Increasing salinization of freshwater limits invasiveness of a live-bearing fish: Insights from behavioral and life-history traits. (1st September 2022) - Zhou, Linjun; Liu, Kai; Zhao, Yu; Cui, Ling; Dong, Chenglong; Wang, Zaizhao
Abstract: Biological invasions and continued salinization of freshwater are two global issues with largely serious ecological consequences. Increasing salinity in freshwater systems, as an environmental stressor, may negatively affect normal life activities in fish. It has been documented that salinity limits the invasive success of alien species by mediating physiological and life-history performances, however, there are few studies on how salinity affects its invasive process via altered behaviors. Using wild-caught invasive western mosquitofish ( Gambusia affinis ) as animal model, in this study, we asked whether gradual increasing salinity affects behaviors (personality and mate choice decision here), life-history traits, as well as the correlation between them by exposing G. affinis to three levels salinity (freshwater, 10 and 20‰). Results showed that, with increased salinity, male tended to be shyer, less active, less sociable, and reduced desire to mate, and female tended to be shyer, less active and lost preferences for the larger male. Furthermore, across salinity treatments, male exhibited reduced body fat content and rising reproduction allocation, however, pregnant female revealed diametrically opposed trends. In addition, the correlation between life-history traits and behaviors was only identified in pregnant female. It seems that either salinity or life-history traits directly affects mosquitofish behaviors. In summary, our results partially emphasize the harmful consequences of salinity on both life-history traits and behavioral performances. These findings provide a novel perspective on how salinity potentially affect fish fitness via altering personalities, mate choice decisions, as well as body condition, and hence supports the idea that salinity could affect the spread of invasive mosquitofish. Graphical abstract: Image 1 Highlights: We evaluate the effects of salinity on fish behavior and life-history traits. Male and female exhibit differential responses to salt stress in some life-history traits. With increased salinity, fish tended to be shyer, less active, and less sociable. Salt stress weakened mating desire (male) and mating preference (female). Salinity led to partially harmful consequences in both behavior and life-history traits.